1994
DOI: 10.1159/000171471
|View full text |Cite
|
Sign up to set email alerts
|

Placebo and Placebo Effect: Their Impact on the Evaluation of Drug Response in Patients

Abstract: Placebo, defined as any therapeutic procedure, without any specific activity, given deliberately to have an effect on a patient, symptom, syndrome or disease, has a great impact in the evaluation of drug response. The possible pathways via which the possible effect brings about clinical and physiological changes remain unknown, but a humoral mechanism seems to be implicated in some placebo effects (e.g. placebo-induced analgesia). The placebo effect depends on many factors, including the type of patient, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our effects in the placebo group may be caused by the regular checkups, encouragement and reminders by the same investigator (NP). This effect has been shown in other studies [34][35][36]. Therefore, we suggest that the placebo effect is very important, even in trials studying effects on morphology.…”
Section: Discussionsupporting
confidence: 76%
“…Our effects in the placebo group may be caused by the regular checkups, encouragement and reminders by the same investigator (NP). This effect has been shown in other studies [34][35][36]. Therefore, we suggest that the placebo effect is very important, even in trials studying effects on morphology.…”
Section: Discussionsupporting
confidence: 76%
“…Since placebo-controlled trials are the only objective way of accurately assessing drug response in patients 16 , any factor contributing to the placebo response will affect the outcome of the study. In general, the positive placebo response in vasomotor trials has been reported to occur in about 20-50% of patients 8,[17][18][19] . The placebo response in the present study was somewhat higher (56.3% reduction in MSVS) than reported in most vasomotor trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have commented that randomized controlled trials in duodenal ulcer have given substantially different placebo healing rates [ 7–9]. It has not been postulated that in duodenal ulcers the frequency of placebo administration might influence the healing process.…”
Section: Introductionmentioning
confidence: 99%